Automated Subfield Volumetric Analysis of Hippocampus in Patients with Drug-Naïve Nondementia Parkinson's Disease. (3rd February 2019) - Park, Jin-Woo; Lee, Chan-Nyoung; Sim, Youngbo; Ham, Hyung-Kyu; Tae, Woo-Suk; Kim, Byung-Jo
Abstract : Several studies used automated segmentation of hippocampal subfield (ASHS) for detailed measurements of anatomic subregions of the hippocampus, especially in the field of neurodegenerative disorders. In this study, we investigated the hippocampal subfield volume of patients with early-stage nondementia PD compared with normal healthy subjects using the ASHS method. A total of 32 subjects were enrolled in this study (sixteen patients with drug naive nondementia PD and sixteen healthy controls). All subjects were scanned with a 1.5 tesla MRI. The volumes of the seven subfields were calculated separately, and then, the whole hippocampal volume was calculated by the summing of CA1, CA2-3, CA4-DG, subiculum, presubiculum, and fimbria, excluding the hippocampal fissure. There were significant diagnosis-by-hemisphere interactive effects on the total hippocampal volume ( F  = 5.197;p = 0.031 ) and the subfield volume of CA2-3 ( F  = 7.586;p = 0.010 ) and CA4-DG ( F  = 7.403;p = 0.011 ). The volumes of CA2-3 ( F  = 19.911;p < 0.001 ), CA4-DG ( F  = 20.273;p < 0.001 ), and total hippocampus ( F  = 10.573;p = 0.005 ) in the left hemisphere were reduced compared to the right hemisphere. We suggest that the hippocampal volume asymmetry, especially in CA4-DG and CA2-3, could be observed in drug-naïve PD patients even in the early stage of the disease.